Revitalizing a village for mental health in watershed area in Central Kalimantan, Indonesia - Missesa, Missesa (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
Most of the inhabitants in Central Kalimantan live in a residential area which is located close to the watershed (DAS). The geography of the watershed is a challenge for affordable health services, particularly in mental health services. Patients with mental disorders who do not get health care services will have a high risk of experiencing recurrence due to withdrawal of medication. There are needs to be solved by various parties to overcome this problem. Mental healthcare delivery in this area is more likely to be effective and sustainable if supported by the secondary level of care in particular the local Health Department. This photo essay pictures our effort to revitalize a village for mental health in watershed area in Central Kalimantan, Indonesia. The concept of